Pengaruh Komponen Akrual dalam Memprediksi Arus Kas Aktivitas Operasi di Masa Depan - Eriska Dwi Apriana; Usep Syaipudin; Yenni Agustina; Einde Evana (CV. Syntax Corporation Indonesia, 2022)
This research aimed to give an empirical evidence about the influence of accrual components in predicting activity of operating future cash flow. This research used 3 accrual components as the independent variables which were changes in receivable, change in payable, and changes in inventory. The data used in this research was secondary data of financial statements of manufacturing companies which were registered in Indonesian Stock Exchange in period 2015 – 2018. Purposive sampling was used in this research and used multiple regression. The results showed that changes in receivable significantly influenced activity of operating cash flow in the future, while changes in payable and changes in inventory didn’t influence activity of operating future cash flow.Changes In Receivable, Changes In Payable, Changes In Inventory, Cash Flow, Future Cash Flow, Accrual Components